1984
DOI: 10.1073/pnas.81.18.5633
|View full text |Cite
|
Sign up to set email alerts
|

Thymine glycol and thymidine glycol in human and rat urine: a possible assay for oxidative DNA damage.

Abstract: Thymine glycol is a DNA damage product of ionizing radiation and other oxidative mutagens. In an attempt to find a noninvasive assay for oxidative DNA damage in individuals, we have developed an HPLC assay for free thymine glycol and thymidine glycol in urine. Our results indicate that humans excrete about 32 nmol of the two glycols per day. Rats, which have a higher specific metabolic rate and a shorter life span, excrete about 15 times more thymine glycol plus thymidine glycol per kg of body weight than' do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
180
2
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(192 citation statements)
references
References 25 publications
8
180
2
2
Order By: Relevance
“…One example, cisthymine glycol (TG) (Fig. 3), has been detected in urine by HPLC (33). We have now developed a GC-MS assay for TG, in which it is quantitated using a d3-labeled internal standard.…”
Section: Urinary Thymine Glycolmentioning
confidence: 99%
“…One example, cisthymine glycol (TG) (Fig. 3), has been detected in urine by HPLC (33). We have now developed a GC-MS assay for TG, in which it is quantitated using a d3-labeled internal standard.…”
Section: Urinary Thymine Glycolmentioning
confidence: 99%
“…It has been suggested that hyperplasia per se can increase the probability of genetic change by increasing the likelihood of mutations arising from normal DNA replication processes or the conversion of DNA lesions produced by oxygen radicals formed endogenously to mutations (3,10). Various estimates have been made of the amounts of spontaneous DNA damage suffered by rats and humans (11,12), but to date, there have been no estimates of the frequency of mutations caused by such DNA damage. Thus, the significance of DNA damage resulting from endogenous reactants such as oxygen radicals remains speculative.…”
Section: Role Of Cell Proliferation In Carcinogenesismentioning
confidence: 99%
“…Oxygen-dependent DNA damage is also observed with aflatoxin B~ [40] and phorbol esters [41,42]. The formation of thymine glycol and thymidine glycol in vivo has been used as a possible assay for oxidative DNA damage [28,43]. Very recently, the formation of 8-hydroxydeoxyguanosine in DNA by oxygen radicals was reported [44][45][46][47][48][49].…”
Section: Oxidative Damage To Dna and Its Relationship To Cancer And Amentioning
confidence: 99%